Ocular metastasis in breast cancer: management of clinical case reports and a literature review - Gao, Jizhuo; Cao, Qian; Liu, Yi; Huang, Mengyao; Li, Man; Xu, Lingzhi (Frontiers in Oncology, 2026)
In recent years, the incidence of breast cancer (BC) and its distant metastases, including ocular metastasis (OM), has continued to rise. However, reports on BC-OM remain scarce. OM is rare and often asymptomatic. It can be easily masked by metastases in other organs, increasing the risk of misdiagnosis, and thus warrants greater clinical attention. In this paper, we describe three cases of BC-OM, review its epidemiological and clinical features, and summarize diagnostic methods and treatment strategies. Our aim is to provide a reference for clinical practice, support standardized management, and ultimately improve patient survival and quality of life (QoL).